Pengaruh Kepemimpinan Transformasional dan Budaya Organisasi terhadap Kinerja Karyawan pada Era Transformasi Digital - Fadly Fadly; Fathy Inat (Indo Publishing, 2026)
Digital transformation has fundamentally changed the workplace environment, business processes, communication patterns, and human resource competency requirements within organizations. These changes require organizations not only to adopt digital technologies but also to develop leadership and organizational cultures that support employee adaptation and performance improvement. This study aims to analyze the influence of transformational leadership and organizational culture on employee performance in the era of digital transformation through a literature review approach using the Systematic Literature Review (SLR) method. Relevant academic literature was collected from various scholarly sources and analyzed descriptively and analytically using thematic synthesis to identify relationship patterns, consistency of findings, and research gaps. The findings indicate that transformational leadership generally has a positive relationship with employee performance through leaders’ ability to develop a shared vision, provide inspiration, stimulate intellectual engagement, enhance employee motivation, and support individual development. Organizational culture also plays an important role in improving employee performance, particularly when organizations develop adaptive, collaborative, innovative, learning-oriented, and change-supportive cultures. However, previous studies demonstrate that the effect of transformational leadership on employee performance is not always consistent and may depend on organizational context and psychological mechanisms such as work motivation, job satisfaction, and organizational commitment. In the context of digital transformation, transformational leadership and organizational culture function as critical socio-organizational factors that determine how effectively technology can be integrated into organizational work processes. The study concludes that improving employee performance in the digital era requires synergy between transformational leadership and an adaptive organizational culture. These findings imply that organizations should integrate digital transformation strategies with leadership development, innovation-oriented cultural development, continuous learning, and employee digital competency enhancement to achieve sustainable performance improvement.